FAKTOR PENENTU TINGKAT PEMAHAMAN AKUNTANSI - Komang Krishna Yogantara (Badung: LPPM Universitas Triatma Mulya, 2020)
This study aims to examine the effect of lectures while working, learning behavior and emotional intelligence on the level of understanding of regular afternoon accounting students of accounting study programs at Triatma Mulya University. The dependent variable in this research is accounting understanding (Y). While the independent variables in this study are lectures while working (X1), learning behavior (X2) and emotional intelligence (X3). The population in this study were all regular evening students of the 2016-2019 accounting study program who are still active at Triatma Mulya University. The sample in this study was selected by purposive sampling method and obtained a sample of 96 students. The research method used is quantitative research and for data analysis using multiple regression analysis. The results of the study stated that lecture while working had a positive effect on accounting understanding, seen from the X1 significance value of 0,000. The positive influence between lectures while working with the level of understanding of accounting identifies that students who are active in carrying out two activities at once, namely lecturing and working together and supporting each other. Furthermore, learning behavior has a positive effect on accounting understanding, seen from the X2 significance value of 0,000. This indicates that the better the student's learning behavior, the better the level of understanding of the student's accounting. While emotional intelligence also has a positive effect on accounting understanding, it can be seen from the X3 significance value of 0.002. This emotional intelligence shows that someone who is able to control his emotional intelligence well, then understanding accounting will also increase.